Love Itself Is Understanding : Hans Urs von Balthasar's Theology of the Saints - Moser, Matthew A. Rothaus (Book collections on Project MUSE., 2016)
Hans Urs von Balthasar (1905-1988) sets out to reunite Truth and holiness by returning the saints to their proper place at the heart of philosophy, theology, and metaphysics. Love Itself is Understanding is one of the first systematic treatments of Balthasar's theology of the saints. Matthew Rothaus Moser presents Balthasar as an alternative to Idealist philosophy, a thinker who develops a religious metaphysics in which the saints' practices of prayer and contemplation are the chief mode of knowing that the Truth of Being is divine love. Love Itself is Understanding casts new light on dominant themes in Balthasar's thought and invites a renewed vision of the theological and metaphysical significance of the spiritual practices of prayer, obedience, and charity.